Two Small RNAs Conserved in Enterobacteriaceae Provide Intrinsic Resistance to Antibiotics Targeting the Cell Wall Biosynthesis Enzyme Glucosamine-6-Phosphate Synthase - Khan, Muna A.; Göpel, Yvonne; Milewski, Slawomir; Görke, Boris (Frontiers in Microbiology, 2016)
Formation of glucosamine-6-phosphate (GlcN6P) by enzyme GlcN6P synthase (GlmS) represents the first step in bacterial cell envelope synthesis. In Escherichia coli, expression of glmS is controlled by small RNAs (sRNAs) GlmY and GlmZ. GlmZ activates the glmS mRNA by base-pairing. When not required, GlmZ is bound by adapter protein RapZ and recruited to cleavage by RNase E inactivating the sRNA. The homologous sRNA GlmY activates glmS indirectly. When present at high levels, GlmY sequesters RapZ by an RNA mimicry mechanism suppressing cleavage of GlmZ. The interplay of both sRNAs is believed to adjust GlmS synthesis to the needs of the cell i.e. to achieve GlcN6P homeostasis. Bacilysin (tetaine) and Nva-FMDP are dipeptide antibiotics that impair cell envelope synthesis by inhibition of enzyme GlmS through covalent modification. However, although taken up efficiently, these antibiotics are less active against E. coli for reasons unknown so far. Here we show that the GlmY/GlmZ circuit provides resistance. Inhibition of GlmS causes GlcN6P deprivation leading to activation of GlmY and GlmZ, which in turn trigger glmS overexpression in a dosage-dependent manner. Mutation of glmY or glmZ disables this response and renders the bacteria highly susceptible to GlmS inhibitors. Thus, E. coli compensates inhibition of GlmS by increasing its synthesis through the GlmY/GlmZ pathway. This mechanism is also operative in Salmonella indicating that it is conserved in Enterobacteriaceae possessing these sRNAs. As GlmY apparently responds to GlcN6P, co-application of a non-metabolizable GlcN6P analogue may prevent activation of the sRNAs and thereby increase the bactericidal activity of GlmS inhibitors against wild-type bacteria. Initial experiments using glucosamine-6-sulfate support this possibility. Thus, GlcN6P analogues might be considered for co-application with GlmS inhibitors in combined therapy to treat infections caused by pathogenic Enterobacteriaceae.